Engineering a branch of the UDP‐precursor biosynthesis pathway enhances the production of capsular polysaccharide in Escherichia coli O5:K4:H4. Issue 8 (24th July 2015) - Cimini, Donatella; Carlino, Elisabetta; Giovane, Alfonso; Argenzio, Ottavia; Dello Iacono, Ileana; De Rosa, Mario; Schiraldi, Chiara
Abstract Escherichia coli K4 produces a capsule with a chemical structure that resembles chondroitin, a molecule with established chondro protective properties. The endogenous genes pgm and galU are involved in the biosynthesis of UDP‐glucose which is a critical intermediate in carbohydrate metabolism and biochemical precursor of UDP‐glucuronic acid. Together with UDP‐N‐acetylgalactosamine, UDP‐glucuronic acid is used as sugar donor for capsule biosynthesis. The aim of the study was to evaluate how a change in the pathways leading to UDP‐glucuronic acid biosynthesis affected capsular polysaccharide production. One additional copy of pgm and galU was introduced in E. coli K4 and in the previously described recombinant strain EcK4r3. A microbioreactor was used to analyse strain performance with parallel batch experiments, demonstrating increased polysaccharide concentrations and providing data that are comparable to those obtained in larger fermenters. Further experiments on a glutamine enriched medium showed an additional 45% increase of capsule production, maybe indicating the need to balance both branches leading to polymer biosynthesis in order to maximize yields. In the effort towards the establishment of a feasible bio‐chondroitin production process this study provides information on how the availability of sugar precursors impacts polysaccharide biosynthesis in E. coli K4, a complex unexplored aspect of a multifaceted process.